Process for producing a temperature rise suppressing material for concrete

CN122940402APending Publication Date: 2026-10-20SHANDONG TIEGONG TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611128719.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-28
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

虽然能够降低混凝土温升,但是会导致混凝土早期强度低,且效果有限;其二,使用缓凝剂

Benefits of technology

(1)本发明方法制得的温升抑制材料结构通过相变材料固化来避免氢氧化钡(氢氧化钙)和氯化铵接触,避免氢氧化钡(氢氧化钙)和氯化铵提前反应,而且采用不同相变温度的相变材料使得该材料在不同温度条件下逐步相变,并通过相变材料含量控制氢氧化钡(氢氧化钙)和氯化铵的接触速率、氯化铵的溶解速率,使得反应缓慢有序;且因氢氧化钡(氢氧化钙)和氯化铵吸热反应导致体系温度降低时,相变材料再次固化,阻碍反应发生;当相变材料再次液化后,氢氧化钡和氯化铵的吸热反应才能进行。这样将整个体系温度控制在相变温度的可控范围内,实现内部温度的精准调控。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

This invention discloses a method for preparing a temperature rise suppressing material for concrete. The preparation method includes: first, adding barium hydroxide or barium hydroxide octahydrate or calcium hydroxide and water to molten lauric acid and then ultrasonically dispersing to obtain emulsion A; second, mixing ammonium chloride with molten palmitic acid or stearic acid and ultrasonically dispersing to obtain emulsion B, then adding it to SAP for thorough wetting and cold air drying to obtain modified SAP microspheres, adding them to emulsion A for ultrasonic dispersion, cooling and solidifying, then shearing and crushing, and air-heat and air-cooling treatment to obtain solid spherical particles C; finally, adding the solid spherical particles C sequentially to an emulsion containing soluble calcium salt and sodium silicate respectively mixed with water and mixed fatty acid glycerides, reacting and drying to obtain the temperature rise suppressing material for concrete. When applied using the method of this invention, the temperature rise suppressing material for concrete can efficiently and actively absorb heat and lower the temperature without significantly affecting the workability, mechanical properties, and construction progress of concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of concrete admixture technology, and specifically to a method for preparing a concrete temperature rise inhibitory material that can effectively reduce the hydration temperature rise of concrete. Background Technology

[0002] After large-volume concrete is poured and formed, a large amount of heat is released during the hydration of the cement inside. Due to the influence of the matrix's heat conduction efficiency and volume size, the internal heat cannot be quickly conducted to the outside, causing a rapid rise in internal temperature. Meanwhile, the outside, due to the interface with air, allows heat to dissipate rapidly, resulting in a large temperature difference between the inside and outside, thus generating thermal stress. When the stress exceeds the tensile strength of the concrete, it will lead to temperature cracks, affecting the safety and durability of the structure. To reduce the temperature difference between the inside and outside of concrete, many methods have been researched. Firstly, using a large amount of fly ash to replace cement. Although this can reduce the temperature rise of concrete, it leads to low early strength and the effect is limited. Secondly, using retarders. Although this delays setting time and reduces early temperature rise, the effect on reducing the peak temperature rise of concrete is limited, and excessive retarder dosage can cause a decrease in concrete strength, affecting project quality. Thirdly, using phase change materials, such as paraffin wax, fatty acids, and TRI, can control the temperature rise to some extent, but the effect is limited. Increasing the dosage to improve temperature rise control will adversely affect concrete performance. In summary, current methods for controlling temperature rise generally suffer from limited effectiveness and significant negative impacts. Summary of the Invention

[0003] To address the problems existing in the above-mentioned background technology, the present invention provides a method for preparing a concrete temperature rise suppression material that can efficiently and actively absorb heat and cool down without significantly affecting the workability, mechanical properties and construction progress of concrete.

[0004] To achieve the above-mentioned objectives, the present invention adopts the following technical solution: A method for preparing a temperature rise suppression material for concrete includes the following steps. (1) Alkaline earth metal hydroxide or its hydrate and water are added to molten lauric acid and mixed, and then dispersed by ultrasonication to form emulsion A; The alkaline earth metal hydroxide is Ba(OH)2 or Ca(OH)2, and the alkaline earth metal hydroxide hydrate is Ba(OH)2·8H2O; The phase transition temperature of the lauric acid is between 41 and 45°C, and the temperature of the molten lauric acid is controlled between 46 and 50°C to ensure that the lauric acid is in a molten state and the temperature is not too high. Before mixing and ultrasonic dispersion, the alkaline earth metal hydroxide or its hydrate and water are preheated. The preheating temperature of the alkaline earth metal hydroxide or its hydrate and water is consistent with the controlled temperature of the molten lauric acid. If the temperature is lower than the phase transition temperature of the lauric acid, the lauric acid will solidify. The ultrasonic dispersion frequency is 20~40kHz, and the ultrasonic dispersion time is 10~20min; (2) Ammonium chloride particles are mixed with molten high-grade saturated fatty acids and ultrasonically dispersed to form emulsion B. Then, it is added to a vacuum-sealed superabsorbent polymer (SAP) resin and fully impregnated to ensure that the pores of the superabsorbent polymer (SAP) resin are fully saturated and absorb emulsion B to obtain SAP microspheres. After the emulsion B is fully absorbed, the SAP microspheres are immediately placed in the air and dried with cold air to ensure that the adsorbent in the pores of the microspheres is solidified and that the particles do not stick together. They are stored below 55°C to avoid melting phase change due to high temperature conditions and the formation of modified SAP microspheres. The higher saturated fatty acid is palmitic acid or stearic acid, wherein the phase transition temperature of palmitic acid is between 58 and 63°C and the phase transition temperature of stearic acid is between 58 and 63°C. Therefore, it is ensured that the temperature during the reaction process is not lower than the phase transition temperature to ensure its molten state. The ultrasonic dispersion frequency is 30~60kHz, and the ultrasonic dispersion time is 20~30min; The controlled temperature during the preparation of the SAP microspheres is not lower than the phase transition temperature of the higher saturated fatty acids used. The superabsorbent polymer (SAP) has a particle size of 50-100 μm and a pore size of 5-10 μm, which enables complete adsorption of emulsion B while making full use of the pore space of SAP. The ammonium chloride particles have a particle size of no more than 2 μm to ensure that they can be fully adsorbed into the SAP microspheres. The cold air drying temperature is not higher than 40℃, and the time is not less than 8 hours; (3) Add the modified SAP microspheres prepared in step (2) to the emulsion A obtained in step (1), disperse it by ultrasonication at no less than 50 kHz for more than 10 min to form a uniformly dispersed suspension, and rapidly cool it down to 40 ℃ or below to solidify it. (4) The particles obtained by shearing and crushing the solidified composite in step (3) are blown into microspheres by strong wind at 45~50℃, and then further cooled into solid spherical particles C by strong wind at 30~40℃. The particle size obtained by shearing and crushing is 100~150μm; The duration of the strong wind at 45~50℃ is controlled to be 5~8 minutes; Strong winds are used to ensure that the solidified and broken composite material is suspended in the air and does not fall to the ground. The purpose of controlling the wind temperature at 45~50℃ is to gradually melt the outermost layer of the Ba(OH)2·8H2O, water, and lauric acid mixture while it is suspended in the air and does not fall to the ground, forming spherical shapes in the liquid state. At 45~50℃, the mixture is kept in a molten state, and under the action of surface tension, it will transform into a microsphere shape. The time is controlled within this range. Then, the temperature is lowered to 30~40℃ to form solid spherical particles. (5) After dissolving soluble calcium salt and sodium silicate in water to form calcium salt aqueous solution and sodium silicate aqueous solution respectively, mixed fatty acid glycerides are added to the two aqueous solutions respectively and then ultrasonically dispersed to form calcium salt emulsion and sodium silicate emulsion respectively; then the solid spherical particles C obtained in step (4) are added to the calcium salt emulsion and uniformly dispersed to form calcium salt suspension; further, the sodium silicate emulsion is slowly added dropwise to the calcium salt suspension for reaction, while stirring and ultrasonically dispersing. The reaction is carried out under water bath conditions of 38~40℃, and the reaction is carried out for 3~4 hours after the addition is completed; then the water bath environment is removed, the temperature is lowered to room temperature of 20~30℃, and the particles are taken out and naturally dried to constant weight to form the concrete temperature rise suppression material particles of the present invention. The soluble calcium salt is calcium nitrate or calcium chloride; The sodium silicate modulus is 2~2.5; The phase transition temperature of the mixed fatty acid glycerides is between 33 and 37°C. The ultrasonic frequency is 20~25kHz, and the ultrasonic dispersion time is 5~10min; The total time for adding the sodium silicate emulsion to the calcium salt suspension is 20-30 minutes, and the ultrasonic dispersion frequency is 15-20 kHz while adding and stirring.

[0005] Furthermore, the mass fractions of the raw material components in each step of the present invention are as follows: In step (1), the effective content of Ba(OH)2 or Ba(OH)2·8H2O is 30-35 parts by mass of Ba(OH)2, 100 parts by mass of water, and 30-40 parts by mass of lauric acid; wherein, the mass of water includes the water content in Ba(OH)2·8H2O, and when the alkaline earth metal hydroxide is Ca(OH)2, it is replaced by an equimolar amount of Ba(OH)2; In step (2), the mass fraction of ammonium chloride is 9-12 parts, the mass fraction of higher saturated fatty acids is 10-15 parts, and the mass fraction of superabsorbent polymer (SAP) is 6-8 parts. In step (5), the total mass fraction of soluble calcium salt and sodium silicate is 10-15 parts, the mass fraction of water in both aqueous solutions is 100 parts, and the mass fraction of mixed fatty acid glycerides added to both aqueous solutions is 20-25 parts; the molar ratio of soluble calcium salt and sodium silicate is 2:1.2-1.5.

[0006] In steps (1) and (2) of this invention, controlling the ratio of barium hydroxide (or calcium hydroxide) and ammonium chloride is to ensure that the reaction can be completed to the greatest extent. Controlling their dosage is to ensure that sufficient temperature rise inhibition effect is achieved without negatively impacting the concrete. If the ammonium chloride content is too high, it will not only release excessive ammonia gas, which will have an adverse effect on the hardening of the concrete, but also generate a large number of chloride ions, affecting the durability of the concrete. Controlling the ratio of barium hydroxide (or calcium hydroxide), ammonium chloride, and higher saturated fatty acids in the phase change material is to make full use of the heat absorption characteristics of the phase change material on the one hand, and to control the ion concentration of barium hydroxide (or calcium hydroxide) and ammonium chloride in the phase change material in the molten state, thereby further controlling its reaction rate and achieving good temperature control. At the same time, since palmitic acid and stearic acid have a wide phase change temperature range, during use, stearic acid with a suitable phase change temperature should be selected according to the volume of large-volume concrete, internal temperature rise, and ambient temperature. If the ambient temperature is high and the internal temperature rise is high, choose palmitic acid or stearic acid with a relatively high phase change temperature. If the ambient temperature is low and the internal temperature rise peak is relatively low, choose palmitic acid or stearic acid with a relatively low phase change temperature.

[0007] In step (5) of this invention, the mixed fatty acid glycerides are in a liquid state while lauric acid is in a solid state. The mixed fatty acid glycerides can erode and fuse with the surface of lauric acid, while lauric acid does not melt and cannot flow, which is conducive to the adhesion of nano-calcium silicate generated on the surface. At the same time, the mixed fatty acid glycerides are used as a binder to form a hard microshell. Meanwhile, the reaction at a temperature of 38~40℃ can ensure the stable and continuous generation of nano-calcium silicate.

[0008] Furthermore, the present invention also provides a concrete temperature rise suppression material prepared by the above method. This concrete temperature rise suppression material has a three-layer structure: the innermost layer is a porous adsorbent using SAP as a porous adsorbent, internally adsorbing a mixture of ammonium chloride particles and palmitic acid or stearic acid; the second layer is a coating layer attached to the SAP surface, mainly composed of Ba(OH)₂ or Ca(OH)₂ or Ba(OH)₂·8H₂O, water, and lauric acid; the third layer is mainly formed on the outside of the second coating layer, using a mixture of fatty acid glycerides, nano-calcium silicate, and sodium silicate as coatings. When the temperature rises due to the hydration reaction in the concrete, the outermost phase change material becomes liquid, further lauric acid becomes liquid, barium hydroxide dissolves to form a solution, and as the temperature further rises, the palmitic acid or stearic acid inside the SAP becomes liquid, ammonium chloride overflows, dissolves in water, absorbs heat, and reacts with barium hydroxide, further absorbing heat and lowering the temperature. After absorbing heat, the temperature drops. When the temperature is lower than the phase change temperature of the phase change material, the phase change material solidifies, and the reaction stops. When the temperature rises and the phase change material reverts to a liquid state, the endothermic reaction occurs again, and this cycle repeats, allowing for precise control of the internal temperature rise under appropriate dosage conditions. During the reaction, ammonia gas is gradually released. However, the ammonia gas is absorbed by the porous structure of the SAP, preventing it from overflowing and adversely affecting the concrete.

[0009] Compared with the prior art, the present invention has the following beneficial effects: (1) The temperature rise suppression material structure prepared by the method of the present invention avoids contact between barium hydroxide (calcium hydroxide) and ammonium chloride by solidifying the phase change material, thus preventing premature reaction between barium hydroxide (calcium hydroxide) and ammonium chloride. Moreover, the use of phase change materials with different phase change temperatures allows the material to undergo phase change gradually under different temperature conditions. The contact rate between barium hydroxide (calcium hydroxide) and ammonium chloride and the dissolution rate of ammonium chloride are controlled by the content of the phase change material, making the reaction slow and orderly. When the system temperature decreases due to the endothermic reaction of barium hydroxide (calcium hydroxide) and ammonium chloride, the phase change material solidifies again, hindering the reaction. Only after the phase change material liquefies again can the endothermic reaction between barium hydroxide and ammonium chloride proceed. In this way, the temperature of the entire system is controlled within the controllable range of the phase change temperature, achieving precise regulation of the internal temperature.

[0010] (2) The purpose of adding a coating layer of mixed fatty acid glycerides and nano-calcium silicate as the outermost layer of the temperature rise suppression material of the present invention is to form a nano-particle attachment layer of hydrated calcium silicate on the particle surface, and at the same time utilize the bonding effect of sodium silicate and mixed fatty acid glycerides to form an integral coating layer. When it is incorporated into concrete, the nano-hydrated calcium silicate can play a nucleation induction role, causing the hydrated calcium silicate in the cement to grow continuously on the surface of the coating layer, improving the density and strength of the coating layer, and preventing the leakage of the internal phase change material after liquefaction. Moreover, as a nucleation induction role, the hydration reaction of hydrated calcium silicate causes the hydration reaction to gradually generate outward from the surface of the temperature rise suppression particles, which is more conducive to precise temperature control and helps the temperature rise suppression material to absorb heat and reduce the hydration reaction temperature. Compared with the previous method of early encapsulation, this method uses the early strength effect of nano-crystal nuclei and the cement hydration effect inside the concrete to further form a coating layer on the surface of microspheres in the early stage of temperature rise, preventing the leakage of phase change material while achieving precise control of temperature rise. Detailed Implementation

[0011] The present invention will be further described below with reference to embodiments, but the scope of protection of the present invention is not limited thereto.

[0012] In each embodiment and comparative example, the component parts are expressed as parts by mass.

[0013] Example 1 The preparation method of a temperature rise suppression material for concrete is as follows: (1) Add 55 parts of Ba(OH)2·8H2O (Ba(OH)2 content is 30 parts) and 75 parts of water (excluding the water content in Ba(OH)2·8H2O) to 40 parts of molten lauric acid, keep the temperature at 46℃, and disperse by ultrasonication at 20kHz for 20min to form emulsion A; The phase transition temperature of lauric acid is 41℃; the temperatures of Ba(OH)2·8H2O and water are consistent with the temperature of lauric acid. (2) Mix 9 parts of ammonium chloride particles with a particle size of 1~2μm with 10 parts of molten palmitic acid and disperse them by ultrasonication at 30kHz for 30min to form emulsion B. Add the emulsion to 6 parts of vacuum-sealed SAP with a particle size of 50μm and a pore size of 5~8μm and fully impregnate it so that the SAP pores can fully absorb the emulsion. During the above process, control the temperature not to be lower than the phase transition temperature of palmitic acid. After full absorption, immediately dry the microspheres in the air with cold air at 40℃ to ensure that the adsorbent in the pores is solidified and the particles do not stick together. Store at room temperature to avoid melting phase transition due to high temperature conditions and forming modified SAP microspheres. The phase transition temperature of the palmitic acid used is 63℃; (3) Add the modified SAP microspheres prepared in step (2) to the emulsion A in step (1), disperse it by ultrasonication at 50 kHz for 30 min to form a uniformly dispersed suspension, and cool it to 40 °C to solidify it. (4) The solidified composite was sheared and crushed into particles with an average particle size of 105 μm. After being subjected to strong wind heat treatment at 45°C and blown into microspheres, it was further cooled with air at 40°C to form solid spherical particles C. (5) Weigh out 15 parts of calcium nitrate and sodium silicate with a modulus of 2 at a molar ratio of 2:1.5. Dissolve them in 100 parts of water to form aqueous solutions. Then add 20 parts of mixed fatty acid glycerides to the calcium nitrate aqueous solution and the sodium silicate aqueous solution respectively. Disperse them by ultrasonication at 20 kHz for 10 min to form calcium nitrate emulsion and sodium silicate emulsion. Then add solid spherical particles C to the calcium nitrate emulsion and disperse them evenly to form a suspension. Further, slowly add the sodium silicate emulsion to the calcium nitrate emulsion for reaction. The total addition time is 30 min. While adding, stir and disperse by ultrasonication at 15 kHz. The reaction is carried out in a water bath at 38 ℃. After 4 h of reaction, remove the water bath environment, cool down to 20 ℃, take out and dry naturally to form temperature rise inhibitor particles. The mixed fatty acid glycerides used are type 34, with a phase transition temperature between 33 and 35°C.

[0014] Example 2 The preparation method of a temperature rise suppression material for concrete is as follows: (1) Add 35 parts Ba(OH)2 and 100 parts water to 30 parts lauric acid in molten state, keep the temperature at 50℃, and disperse by ultrasonication at 40kHz for 10min to form emulsion A; The phase transition temperature of lauric acid is 44.7℃; the temperatures of Ba(OH)2·8H2O and water are consistent with those of lauric acid. (2) Mix 12 parts of ammonium chloride particles with a particle size of 0.5~1μm with 15 parts of molten stearic acid and disperse them by ultrasonication at 60kHz for 20min to form emulsion B. Add the emulsion to 8 parts of vacuum-sealed SAP with a particle size of 100μm and a pore size of 7~10μm and fully impregnate it so that the SAP pores can fully absorb the emulsion. During the above process, control the temperature not to be lower than the phase transition temperature of stearic acid. After full absorption, immediately dry the microspheres in the air with cold air at 30℃ to ensure that the adsorbent in the pores is solidified and that the particles do not stick together. Store at room temperature to avoid melting phase transition due to high temperature conditions and forming modified SAP microspheres. The stearic acid used has a phase transition temperature of 58℃; (3) Add the modified SAP microspheres prepared in step (2) to the emulsion A in step (1), disperse it by ultrasonication at 60 kHz for 15 min to form a uniformly dispersed suspension, and cool it to room temperature of 28 ℃ to allow it to solidify. (4) The solidified composite was sheared and crushed into particles with an average particle size of 150 μm. After being blown into microspheres by strong wind at 50°C, it was further cooled into solid spherical particles C by strong wind at 30°C. (5) Weigh out 10 parts of calcium chloride and sodium silicate with a modulus of 2.5 at a molar ratio of 2:1.2. Dissolve them in 100 parts of water to form aqueous solutions. Then add 25 parts of mixed fatty acid glycerides to the calcium salt aqueous solution and the sodium silicate aqueous solution respectively. Disperse the mixture by ultrasonication at 25 kHz for 5 min to form calcium salt emulsion and sodium silicate emulsion. Then add solid spherical particles C to the calcium salt emulsion and disperse them evenly to form a suspension. Further, slowly add the sodium silicate emulsion to the calcium salt emulsion for reaction. The total addition time is 20 min. While adding, stir and disperse by ultrasonication at 20 kHz. The reaction is carried out in a water bath at 39 ℃. After the reaction is 3 h, remove the water bath environment, cool down to 30 ℃, take out and dry naturally to form temperature rise inhibition particles. The mixed fatty acid glycerides used are type 36, with a phase transition temperature between 35 and 37°C.

[0015] Example 3 The preparation method of a temperature rise suppression material for concrete is as follows: (1) Add 33 parts Ba(OH)2 and 100 parts water to 35 parts lauric acid in molten state, keep the temperature at 48℃, and disperse by ultrasonication at 30kHz for 15min to form emulsion A; The phase transition temperature of lauric acid is 42℃; Ba(OH)2·8H2O, the temperature of the water and the temperature of the lauric acid should be kept consistent; (2) Mix 10 parts of ammonium chloride particles with a particle size of 0.5~1μm with 12 parts of molten palmitic acid and disperse them by ultrasonication at 40kHz for 25min to form emulsion B. Add the emulsion to 7 parts of vacuum-sealed SAP with a particle size of 60μm and a pore size of 8~10μm and fully impregnate it so that the SAP pores can fully absorb the emulsion. During the above process, control the temperature not to be lower than the phase transition temperature of stearic acid. After full absorption, immediately dry the microspheres in the air with cold air at 20℃ to ensure that the adsorbent in the pores is solidified and the particles do not stick together. Store at 20℃ to avoid melting phase transition due to high temperature conditions and forming modified SAP microspheres. The phase transition temperature of the palmitic acid used is 60℃; (3) Add the modified SAP microspheres prepared in step (2) to the emulsion A in step (1), disperse it by ultrasonication at 65 kHz for 10 min to form a uniformly dispersed suspension, and cool it to room temperature of 22 ℃ to allow it to solidify. (4) The solidified composite was sheared and crushed into particles with an average particle size of 120 μm. After being blown into microspheres by strong wind at 48°C, it was further cooled into solid spherical particles C by strong wind at 35°C. (5) Weigh out 12 parts of calcium chloride and sodium silicate with a modulus of 2.2 at a molar ratio of 2:1.3. Dissolve them in 100 parts of water to form aqueous solutions. Then add 24 parts of mixed fatty acid glycerides to the calcium salt aqueous solution and the sodium silicate aqueous solution respectively. Disperse the mixture by ultrasonication at 23 kHz for 8 min to form calcium salt emulsion and sodium silicate emulsion. Then add solid spherical particles C to the calcium salt emulsion and disperse them evenly to form a suspension. Further, slowly add the sodium silicate emulsion to the calcium salt emulsion for reaction. The total addition time is 25 min. While adding, stir and disperse by ultrasonication at 16 kHz. The reaction is carried out in a water bath at 40 ℃. After 3.6 h of reaction, remove the water bath environment, cool down to 22 ℃, take out and dry naturally to form temperature rise inhibition particles.

[0016] The mixed fatty acid glycerides used are type 34, with a phase transition temperature between 33 and 35°C.

[0017] Example 4 The difference from Example 3 is that barium hydroxide is replaced with an equimolar amount of calcium hydroxide.

[0018] Comparative Example 1 Compared with Example 3, only steps (1) and (2) are performed; in step (2), SAP is not used, and the material is directly cooled and solidified, and then crushed into particles; in step (1), the material is also directly cooled and solidified and then crushed into particles. The particles from steps (1) and (2) are then added to the concrete for use.

[0019] Comparative Example 2 Compared with Example 3, only step (2) is performed; in step (2), SAP is not used, and the material is directly cooled and solidified, and then broken into particles.

[0020] Comparative Example 3 Compared with Example 3, the amount of barium hydroxide in step (1) was increased to 49.5 parts, the amount of ammonium chloride in step 2 was increased to 15 parts, and the rest remained the same as in Example 3.

[0021] Comparative Example 4 Compared with Example 3, the content of mixed fatty acid glycerides in step (5) is 10 parts.

[0022] Comparative Example 5 Compared with Example 3, the content of mixed fatty acid glycerides in step (5) is 40 parts.

[0023] Comparative Example 6 Compared with Example 3, step (5) is omitted, and the solid spherical particles C obtained in step (4), an equal mass of nano-hydrated calcium silicate, and mixed fatty acid glycerides are directly added to the concrete.

[0024] Comparative Example 7 Compared to Example 3, equal masses of barium hydroxide, ammonium chloride, lauric acid, palmitic acid, mixed fatty acid glycerides, water, and nano-calcium silicate were directly incorporated into concrete production in the proportions of Example 3.

[0025] Comparative Example 8 Concrete was prepared by replacing 30% of cement with Class F, Grade II fly ash.

[0026] Comparative Example 9 Add commercially available retarder (Jiangsu Aolaite) at the median of the recommended dosage.

[0027] The standard concrete mix design is shown in Table 1.

[0028] Table 1. Reference Concrete Mix Proportion (kg / m³) 3 The cement used is ordinary Portland cement P.O42.5, the river sand has a fineness modulus of 2.6, the crushed stone is limestone, and the polycarboxylate superplasticizer has a water reduction rate of 27%, with a recommended dosage of 2%. The dosage of the temperature rise suppressing material prepared in this invention is controlled at 2% of the cement content, that is, 7.2 kg / m³ is added to the base concrete. 3 Temperature rise suppression materials.

[0029] The temperature rise suppression materials prepared in the above different embodiments and comparative examples were used in a 1m×1m×1m large-volume concrete. The temperature rise change of the concrete during the entire hardening process was detected to obtain the internal temperature rise peak. 100×100×100mm test blocks were cut from the concrete to test their 28-day compressive strength. The results are shown in Table 2.

[0030] Table 2 Concrete Properties From the data in Table 2, we can conclude that: Compared to Example 3, Comparative Example 1 showed a worse temperature rise suppression effect, and the 28-day compressive strength decreased significantly. This indicates that directly adding barium hydroxide and ammonium chloride after solidification severely affects the mechanical properties of concrete and negates the temperature rise suppression effect. This is because, when the concrete temperature rises to the point where the phase change material melts after adding both, on the one hand, the phase change material penetrates into the concrete, affecting its strength development. On the other hand, the lauric acid in the barium hydroxide solution dissolves first, releasing barium hydroxide, and the dissolution of barium hydroxide actually increases the OH- ions in the solution. - The increased concentration of ammonium chloride raises the alkalinity of the system, which in turn accelerates cement hydration, causing a rapid rise in internal temperature and ultimately resulting in a larger peak temperature increase. When the temperature rise exceeds the phase transition temperature of palmitic acid, ammonium chloride rapidly dissolves in the concrete's aqueous solution and reacts with calcium hydroxide in the concrete to produce calcium chloride and ammonia. This reaction continues, reducing the temperature rise. Although the endothermic reaction has a certain degree of temperature-inhibiting effect, the continuous reaction and cooling severely affect the normal hydration of cement. Furthermore, the large amount of calcium chloride produced after the reaction has finished has an early-strength effect. This leads to a further rapid reaction after the hydration has been severely inhibited, causing an increase in temperature and disrupting the overall strength-growth reaction system, ultimately resulting in a rapid decrease in strength.

[0031] Compared with Example 3, Comparative Example 2 showed a worse temperature rise suppression effect, and the 28-day compressive strength decreased significantly. After palmitic acid reached its phase transition temperature, its melting caused ammonium chloride to precipitate and rapidly dissolve in water. This endothermic dissolution and cooling effect were present, but due to the lack of resistance, the dissolution process continued. During dissolution, it reacted with calcium hydroxide to form calcium chloride, which significantly accelerated the hydration of concrete in the later stages, leading to increased shrinkage. The temperature rise control effect failed, and the strength decreased rapidly in the later stages.

[0032] Compared with Example 3, Comparative Example 3 showed a significant inhibition of temperature rise and a decrease in compressive strength. This is because excessive addition increases density and concentration, accelerates the reaction, and generates a large amount of ammonia gas. Consequently, SAP cannot absorb a large amount of ammonia gas, causing it to overflow into the concrete and affecting its compressive strength.

[0033] Compared to Example 3, Comparative Examples 4 and 5 showed a worse temperature rise inhibition effect, with a significant decrease in 28-day compressive strength. Controlling the amount of mixed fatty acid glycerides was to control the particle size of the generated calcium silicate hydrate, enabling it to act as a nucleation agent while synergistically forming a strong outer shell with sodium silicate, ensuring structural stability during concrete mixing. When the content of mixed fatty acid glycerides was high, it was prone to breakage during concrete mixing, negatively impacting early cement hydration and producing the same negative effect as Comparative Example 1, failing to provide effective temperature rise inhibition. When the content was low, the calcium silicate formed a large-sized covering layer, losing its nucleation effect, preventing hydration products from adhering and growing extensively on its surface. This resulted in the outflow of internal phase change materials and dissolved barium hydroxide and ammonium chloride due to its porous structure, affecting interfacial strength and the normal hydration reaction of cement. Similarly, it produced negative effects similar to Comparative Example 1.

[0034] Compared with Example 3, Comparative Example 6 showed a worse effect in inhibiting temperature rise, and the 28-day compressive strength decreased significantly. This is because although the direct incorporation of crystal nuclei has a nucleation effect, it cannot form a mixed coating layer with certain bonding properties with sodium silicate and mixed fatty acid glycerides. Similarly, it is easily damaged during concrete mixing, affecting the normal early hydration of cement, and introducing a large amount of ammonia gas, which affects the mechanical properties of concrete.

[0035] Compared to Example 3, Comparative Example 7 showed a worse temperature rise inhibition effect, and the 28-day compressive strength decreased significantly. This is because ammonium chloride participates in the reaction from the initial stage, dissolving and absorbing heat, which continues to occur, causing extreme cooling inside the concrete. This severely affects the normal hydration of cement, disrupting its normal hydration process and leading to a rapid decrease in strength. The ammonia gas generated during the reaction also has an adverse effect on the concrete. After the ammonium chloride reaction is complete, the resulting calcium chloride has an early strength-inhibiting effect, rapidly raising the temperature. The inhibitory effect of the phase change material is limited, thus the temperature rise inhibition effect is worse. Furthermore, the large amount of phase change material dispersed in the concrete causes a sharp decrease in its strength.

[0036] Compared with Example 3, Comparative Example 8 shows that the addition of 30% fly ash to replace cement significantly reduces the strength of the concrete, and the effect of inhibiting temperature rise is not as good as that of using a temperature rise inhibitor. Moreover, the use of large amounts of fly ash is detrimental to early strength.

[0037] Compared with Example 3, Comparative Example 9 shows that the addition of a retarder significantly reduces the compressive strength of the concrete and is detrimental to temperature rise control. This is mainly because while the retarder delays the setting time, it cannot regulate the hydration process after solidification, thus its effect on inhibiting temperature rise is not significant.

Claims

1. A method for preparing a temperature rise suppression material for concrete, characterized in that, Includes the following steps (1) Alkaline earth metal hydroxide or its hydrate and water are added to molten lauric acid and mixed, and then dispersed by ultrasonication to form emulsion A; The alkaline earth metal hydroxide is Ba(OH)2 or Ca(OH)2, and the alkaline earth metal hydroxide hydrate is Ba(OH)2·8H2O; The phase transition temperature of the lauric acid is between 41 and 45°C, and the temperature of the molten lauric acid is controlled between 46 and 50°C. Before mixing and ultrasonic dispersion, the alkaline earth metal hydroxide or its hydrate and water are preheated. The preheating temperature of the alkaline earth metal hydroxide or its hydrate and water is consistent with the temperature control of the molten lauric acid. (2) Ammonium chloride particles are mixed with molten high-grade saturated fatty acids and dispersed by ultrasonication to form emulsion B. Then, it is added to a vacuum-sealed superabsorbent resin (SAP) and fully impregnated so that the pores of the superabsorbent resin (SAP) are fully saturated and absorb emulsion B to obtain SAP microspheres. After the emulsion B is fully absorbed, the SAP microspheres are immediately placed in the air and dried with cold air and stored below 55°C to form modified SAP microspheres. The higher saturated fatty acid is palmitic acid or stearic acid, wherein the phase transition temperature of palmitic acid is between 58 and 63°C, and the phase transition temperature of stearic acid is between 58 and 63°C. The controlled temperature during the preparation of the SAP microspheres is not lower than the phase transition temperature of the higher saturated fatty acids used. (3) Add the modified SAP microspheres prepared in step (2) to the emulsion A obtained in step (1), disperse it by ultrasonication at no less than 50 kHz for more than 10 min to form a uniformly dispersed suspension, and rapidly cool it down to 40 ℃ or below to solidify it. (4) The particles obtained by shearing and crushing the solidified composite in step (3) are blown into microspheres by strong wind at 45~50℃, and then further cooled into solid spherical particles C by strong wind at 30~40℃. (5) After dissolving soluble calcium salt and sodium silicate in water to form calcium salt aqueous solution and sodium silicate aqueous solution respectively, mixed fatty acid glycerides are added to the two aqueous solutions respectively and then ultrasonically dispersed to form calcium salt emulsion and sodium silicate emulsion respectively; then the solid spherical particles C obtained in step (4) are added to the calcium salt emulsion and uniformly dispersed to form calcium salt suspension; further, the sodium silicate emulsion is slowly added dropwise to the calcium salt suspension to carry out the reaction, while stirring and ultrasonically dispersing. The reaction is carried out under water bath conditions of 38~40℃, and the reaction is carried out for 3~4 hours after the addition is completed; then the water bath environment is removed, the temperature is lowered to room temperature of 20~30℃, and the particles are taken out and naturally dried to constant weight to form the concrete temperature rise inhibition material particles; The phase transition temperature of the mixed fatty acid glycerides is between 33 and 37°C.

2. The preparation method according to claim 1, characterized in that, The ultrasonic dispersion frequency in step (1) is 20~40kHz, and the ultrasonic dispersion time is 10~20min; The ultrasonic dispersion frequency in step (2) is 30~60kHz, and the ultrasonic dispersion time is 20~30min; In step (5), after adding mixed fatty acid glycerides to the aqueous solution, ultrasonic dispersion is performed at 20-25 kHz for 5-10 min.

3. The preparation method according to claim 1, characterized in that, The superabsorbent polymer (SAP) resin in step (2) has a particle size of 50-100 μm and a pore size in the range of 5-10 μm; the ammonium chloride particles have a particle size of no more than 2 μm. The cold air drying temperature is no higher than 40℃, and the time is no less than 8 hours.

4. The preparation method according to claim 1, characterized in that, The particle size obtained by shearing and crushing in step (4) is 100~150μm; The duration of the strong wind at 45-50°C is controlled to be 5-8 minutes.

5. The preparation method according to claim 1, characterized in that, The soluble calcium salt mentioned in step (5) is calcium nitrate or calcium chloride; The sodium silicate modulus is 2~2.5; The total time for adding the sodium silicate emulsion to the calcium salt suspension is 20-30 minutes, and the ultrasonic dispersion frequency is 15-20 kHz while adding and stirring.

6. The preparation method according to claim 1, characterized in that, The mass fractions of the raw material components in each of the above steps are as follows: In step (1), the effective content of Ba(OH)2 or Ba(OH)2·8H2O is 30-35 parts by mass of Ba(OH)2, 100 parts by mass of water, and 30-40 parts by mass of lauric acid; wherein, the mass of water includes the water content in Ba(OH)2·8H2O, and when the alkaline earth metal hydroxide is Ca(OH)2, it is replaced by an equimolar amount of Ba(OH)2; In step (2), the mass fraction of ammonium chloride is 9-12 parts, the mass fraction of higher saturated fatty acids is 10-15 parts, and the mass fraction of superabsorbent polymer (SAP) is 6-8 parts. In step (5), the total mass fraction of soluble calcium salt and sodium silicate is 10-15 parts, the mass fraction of water in both aqueous solutions is 100 parts, and the mass fraction of mixed fatty acid glycerides added to both aqueous solutions is 20-25 parts; the molar ratio of soluble calcium salt and sodium silicate is 2:1.2-1.

5.

7. A temperature rise suppressing material for concrete prepared by any one of claims 1 to 6.

8. The concrete temperature rise suppression material according to claim 7, characterized in that, The concrete temperature rise suppression material particles have a three-layer structure: the innermost layer is a porous adsorbent with SAP as the adsorbent, which adsorbs a mixture of ammonium chloride particles and palmitic acid or stearic acid; the second layer is a coating layer attached to the surface of SAP, mainly composed of Ba(OH)2 or Ca(OH)2 or Ba(OH)2·8H2O, water and lauric acid as coatings; the third layer is a coating layer formed on the outside of the second coating layer, composed of mixed fatty acid glycerides, nano-calcium silicate and sodium silicate.